Exploring nanobubble technology for enhanced anaerobic digestion of thermal-hydrolysis pre-treated sewage sludge - Lyu, Tao; Wu, Fei; Nasar, Nasreen; Li, Xin; Jarvis, Peter; Bajón Fernández, Yadira (Elsevier, 2024)
Nanobubble technology was used to enhance anaerobic digestion (AD) of thermal-hydrolysis pre-treated sewage sludge for bioenergy recovery. The prepared air, CO2, and H2 nanobubble solutions, with concentrations of 9.88–10.2 × 107 bubbles/mL, remained stable for at least 7 days. After adding them into AD reactors, significantly higher CH4 production (37.1 %) was observed for the CO2 nanobubble treatment, followed by air (25.6 %) and H2 (14.5 %) nanobubble treatments, compared to the control group. CO2 nanobubble treatment performed the best in improving acidogenesis/acetogenesis, resulting in significantly higher volatile fatty acid generation during the initial 3–4 days. A comparison of reactors supersaturated and non-saturated with oxygen has demonstrated most of the biogas uplift observed to result from the nanobubbles rather than from initial oxygen soluble levels, demonstrating the crucial role of nanobubbles in upgrading AD. This study demonstrates, for the first time, that nanobubbles can provide additional benefits when combined with stablished sludge pre-treatment technologies.
Keywords: Biogas production; Resource recovery; Sludge treatment; Waste management; Ultrafine bubble; 4004 Chemical Engineering; 40 Engineering; 4011 Environmental engineering; 4103 Environmental biotechnology